2008
DOI: 10.2106/jbjs.f.01494
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Loading Compared with Shock Wave Treatment for Chronic Insertional Achilles Tendinopathy

Abstract: Eccentric loading as applied in the present study showed inferior results to low-energy shock wave therapy as applied in patients with chronic recalcitrant tendinopathy of the insertion of the Achilles tendon at four months of follow-up. Further research is warranted to better define the indications for this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
294
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(313 citation statements)
references
References 41 publications
7
294
1
6
Order By: Relevance
“…Additionally, combination of eccentric training with ESWT was shown to be more beneficial when compared with eccentric training alone. In an RCT consisting of 68 patients with chronic Achilles tendinopathy and a history of failed management, Rompe et al 16,17 found that combining ESWT with eccentric training yielded significant improvements in pain and function at a 4-month follow-up in midportion Achilles tendinopathy and at 1 year in insertional Achilles tendinopathy. These results should encourage clinicians to administer ESWT as an adjunct to eccentric training.…”
Section: Shock Wave Therapymentioning
confidence: 99%
“…Additionally, combination of eccentric training with ESWT was shown to be more beneficial when compared with eccentric training alone. In an RCT consisting of 68 patients with chronic Achilles tendinopathy and a history of failed management, Rompe et al 16,17 found that combining ESWT with eccentric training yielded significant improvements in pain and function at a 4-month follow-up in midportion Achilles tendinopathy and at 1 year in insertional Achilles tendinopathy. These results should encourage clinicians to administer ESWT as an adjunct to eccentric training.…”
Section: Shock Wave Therapymentioning
confidence: 99%
“…The parameters evaluated were PPT [18] and tenderness at 3 kg, as assessed using an algometer and a numeric rating scale [19]. Both measurements were performed by the same investigator.…”
Section: Randomization and Blinding Proceduresmentioning
confidence: 99%
“…Local anesthesia is not used. Applications are done at weekly intervals for three to four applications, and patients are followed for at least 3-4 months after last application [37]. This protocol has been used in ESWT for Achilles tendinopathy trials.…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%